2001
DOI: 10.1128/mcb.21.21.7495-7508.2001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Poly(A) Signal Transduction to RNA Polymerase II In Vitro

Abstract: Termination of transcription by RNA polymerase II usually requires the presence of a functional poly(A) site. How the poly(A) site signals its presence to the polymerase is unknown. All models assume that the signal is generated after the poly(A) site has been extruded from the polymerase, but this has never been tested experimentally. It is also widely accepted that a "pause" element in the DNA stops the polymerase and that cleavage at the poly(A) site then signals termination. These ideas also have never bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 84 publications
2
45
0
2
Order By: Relevance
“…This result may be related to the recent findings using in vitro assays (Tran et al 2001) and EM visualization of RNAP II transcription (Osheim et al 1999(Osheim et al , 2002 to show that cleavage is not a prerequisite for termination in higher eukaryotic cells. Our results support a model in which termination in eukaryotes is dependent on an earlier event, such as recognition of polyadenylation signals by the processing machinery.…”
Section: Discussionsupporting
confidence: 68%
“…This result may be related to the recent findings using in vitro assays (Tran et al 2001) and EM visualization of RNAP II transcription (Osheim et al 1999(Osheim et al , 2002 to show that cleavage is not a prerequisite for termination in higher eukaryotic cells. Our results support a model in which termination in eukaryotes is dependent on an earlier event, such as recognition of polyadenylation signals by the processing machinery.…”
Section: Discussionsupporting
confidence: 68%
“…This was accomplished using a HeLa nuclear extraction protocol (Tran et al 2001) and verified by immunoblots probed with the CCT1 primary antibody (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…The HeLa cells were lysed following the HeLa nuclear extraction protocol (Tran et al 2001). Briefly, the pellet was washed with iced phosphate buffer (137 mM NaCl, 2.68 mM KCl, 4.29 mM Na 2 HPO 4 , and 1.47 mM KH 2 PO 4 ).…”
Section: Tric Purification From Hela Cellsmentioning
confidence: 99%
“…To investigate the basal mechanism of poly(A)-dependent pausing and termination, we placed poly(A) signals into foreign sequence backgrounds, taking particular care to ensure that DNA downstream of the poly(A) signal was devoid of any natural elements that might modify poly(A) signal activity (Tran et al 2001;Orozco et al 2002). It was such experiments that previously showed that polymerase density first rises and then falls after crossing the poly(A) signal, reflecting poly(A)-dependent pausing of the polymerases followed by release (Orozco et al 2002).…”
Section: Introductionmentioning
confidence: 99%